Hydronephrosis due to bladder carcinoma - Tayfur, Mahir; Balcı, Mecdi (Journal of Surgery and Medicine, 2022)
Giant hydronephrosis is a rare entity that most often develops due to obstruction at the ureteropelvic junction. The other etiologic factors include bladder and ureter tumors. Giant hydronephrosis can cause long-term complications such as hypertension, renal failure, rupture of the kidney, and malignant change if left undiagnosed or diagnosed late. A 73-year-old male patient was admitted to the hospital with complaints of difficulty in urination and brown colored urine. The patient's hemoglobin and hematocrit levels were low. Radiologically, there was widespread cystic development in the right kidney, a giant hydronephrosis, and a mass in the bladder. In the surgical material sent after the diagnosis of urothelial carcinoma by bladder biopsy, there was urothelial carcinoma in the bladder and right ureter. Since hydronephrosis may develop due to bladder and ureter tumors, which may result in nephrectomy, the early diagnosis of these tumors will reduce such serious complications. The early diagnosis and treatment of a giant hydronephrosis will increase the patient's quality of life by minimizing complications such as hypertension, kidney failure, and kidney rupture.